2008
DOI: 10.1371/journal.pone.0001861
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Transglutaminase 2 Is Catalytically Inactive, but Is Transiently Activated upon Tissue Injury

Abstract: Transglutaminase 2 (TG2) is a multifunctional mammalian protein with transamidase and signaling properties. Using selective TG2 inhibitors and tagged nucleophilic amine substrates, we show that the majority of extracellular TG2 is inactive under normal physiological conditions in cell culture and in vivo. However, abundant TG2 activity was detected around the wound in a standard cultured fibroblast scratch assay. To demonstrate wounding-induced activation of TG2 in vivo, the toll-like receptor 3 ligand, polyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
198
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(218 citation statements)
references
References 48 publications
11
198
0
4
Order By: Relevance
“…TG2 was shown to bind to extracellular matrix components and also to β1-and β3-integrins or other cell surface receptors or co-receptors such as platelet-derived growth factor receptor (PDGFR) or syndecan-4 on the cell surface, enhancing cell adhesion [27,[38][39][40]. Interestingly, some of the ECM-related TG2 functions are independent of enzyme activity [5,41]. Here we demonstrate that S100A4 have a role in TG2-mediated cell adhesion as measured by a real-time impedance-based assay: immobilizing TG2 and S100A4 on fibronectin-coated plates (in the presence of Ca 2+ ) significantly increased cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG2 was shown to bind to extracellular matrix components and also to β1-and β3-integrins or other cell surface receptors or co-receptors such as platelet-derived growth factor receptor (PDGFR) or syndecan-4 on the cell surface, enhancing cell adhesion [27,[38][39][40]. Interestingly, some of the ECM-related TG2 functions are independent of enzyme activity [5,41]. Here we demonstrate that S100A4 have a role in TG2-mediated cell adhesion as measured by a real-time impedance-based assay: immobilizing TG2 and S100A4 on fibronectin-coated plates (in the presence of Ca 2+ ) significantly increased cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In the extracellular matrix, where the concentration of Ca 2+ is generally high and the level of GTP is relatively low, one would expect that TG2 has a high cross-linking activity. However, several evidences demonstrate that ECM-or plasma membrane-bound TG2 is mainly inactive due to disulfide bond formation and protein-protein interactions and only becomes activated by the induction of certain stressors [4][5][6]. In the extracellular milieu, the effect of TG2 on cell-ECM adhesion and cell migration depends on its interaction with ECM-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in mice have shown that extracellular TG2 exists predominantly in a catalytically inactive form under normal conditions but can become activated through inflammation or in the presence of a reducing agent (18,29). The latter observation suggests that the enzyme is inactivated by oxidation in the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine oxidation inactivates TG2 (17,27,28), and intramolecular disulfide bond formation presumably leads to TG2 inactivation in the extracellular environment (18,29). To study the structural properties of oxidized TG2, we also performed local-exchange analysis on iTG2, which had been incubated with oxidized glutathione before the addition of Ca 2+ .…”
Section: Disulfide Bond Formation In Itg2 Prevents the Stabilizing Efmentioning
confidence: 99%
“…Low Ca 2ϩ concentration and high GTP/GDP concentration in the cytosol typically prevent TG2 activation within cells. Despite conditions in the extracellular milieu that favor activation, extracellular TG2 also appears to be predominantly inactive under normal conditions but can be activated by certain types of inflammation and cell injury (9).…”
Section: Human Transglutaminase 2 (Tg2)mentioning
confidence: 99%